Class and Parents' Agency in West Virginia: Between Choices and Rights - Melissa Sherfinski (Arizona State University, 2013)
Universal pre-kindergarten (UPK) is a popular reform in West Virginia, offering part-time readiness-oriented instruction for four-year-olds and some three-year-olds with special needs. The reform joins public school sites and community partners (private preschool and/or Head Start resources) in the goal of pre-kindergarten for all eligible children, and has targeted the struggling lower-middle class. UPK may position parents between choices and rights by providing discrepant public and private choices for families who do not qualify for the Head Start strand while naming access "universal". In this case study, I examine the context of access in relation to the discourses and politics of neoliberal globalism. Neoliberal globalism has shaped West Virginia's UPK policy towards producing particular childhoods and roles for teachers and parents in service to the economic growth of the state. Specifically, I analyze the role of social class dynamics among lower-middle class parents who sought readiness opportunities in one UPK community. The results indicate that Bourdieu's theory of social reproduction is relevant. Lower-middle class parents were active and instrumental choosers within the hybrid market system. Given two groups of lower-middle class participants (RMC-recent members of the lower-middle class descended from the middle class and HMC-historical members of the lower-middle class), RMC advantageously engaged resources traditionally designated for poor and working class families while HMC used  social networks built locally over time to support their choice-making. In order to re-think West Virginia UPK's position towards cultural pluralism and social justice, I suggest several possibilities in the areas of policy, community deliberation, and educational practice.